Axillary ultrasound during neoadjuvant systemic therapy in triple-negative breast cancer patients. Issue 130 (September 2020) - Candelaria, Rosalind P.; Adrada, Beatriz E.; Hess, Kenneth; Santiago, Lumarie; Lane, Deanna L.; Thompson, Alastair M.; Moulder, Stacy L.; Huang, Monica L.; Arribas, Elsa M.; Rauch, Gaiane M.; Leung, Jessica W.T.; Symmans, W. Fraser; et al.
Highlights: Metastasis to axillary nodes is a predictive biomarker in TNBC patients. AUS has high diagnostic performance in detecting nodal metastasis in TNBC. >4 abnormal nodes on mid-treatment AUS associates with residual disease post-NAST. Abstract: Purpose: To investigate the value of performing mid-treatment axillary ultrasound (AUS) in triple-negative breast cancer (TNBC) patients who are undergoing neoadjuvant systemic therapy (NAST) by determining the optimal cutoff number of abnormal nodes associated with residual nodal disease on surgical pathology. Materials and methods: This sub-study, an interim analysis of an ongoing single-institution clinical trial enrolling patients with stage I-III TNBC, included 106 patients. Number of abnormal nodes at mid-treatment was assessed and recorded by experienced breast radiologists, who empirically categorized lymph nodes using a binary approach of sonographically-normal versus abnormal. Pathologic lymph node positivity was defined as presence of macrometastasis or micrometastasis in ≥1 axillary node from sentinel lymph node biopsy and/or axillary lymph node dissection. Results: Of 106 patients, 26 (25 %) had residual nodal disease and 80 (75 %) had no nodal disease at surgery. Median number of abnormal nodes at mid-treatment was 5 (standard deviation [SD], 5) for patients with residual nodal disease and 0 (SD, 2) for patients with no nodal disease at surgery (p < 0.0001). TNBC patients with >4 abnormal nodes at mid-treatment had a significantly higher chance of being node-positive at surgery (AUC = 0.908, p < 0.0001; PPV = 90 %). Conclusion: Our data suggest that a cutoff of >4 abnormal nodes on mid-treatment AUS is associated with residual disease post-NAST. If our findings are substantiated by subsequent analyses, then mid-treatment AUS could be used to identify patients unlikely to achieve nodal pathologic complete response and who should be offered alternative therapy.